A Comprehensive Review of the Brain–Gut Microbiota System in Traumatic Brain Injury: Mechanisms, Outcomes, and Emerging Interventions - Albert, Venencia; Kedia, Shweta; Subramanian, Arulselvi (Indian Journal of Neurosurgery, 2025)
Traumatic brain injury (TBI) has profound effects that extend beyond the brain, affecting other body systems via secondary pathways and leading to various complications, including gastrointestinal (GI) dysfunction during and after hospitalization. While advances in TBI management have improved overall outcomes, the absence of effective treatments for these systemic effects highlights the urgent need for innovative therapeutic strategies. A critical aspect in this context is the brain–gut axis (BGA), a bidirectional communication network connecting the brain and GI system through complex neuronal, hormonal, and immune pathways. TBI results in increased intestinal permeability and a hypercatabolic state leading to bacterial translocation, immune dysregulation, septic complications, and multiorgan failure. These complications significantly heighten the risk of morbidity and mortality in TBI patients. Emerging evidence suggests that gut dysbiosis plays a pivotal role in post-TBI complications. The gut microbiome, a diverse community of commensal microorganisms, is integral to gut physiology, performing key functions such as metabolic regulation, maintaining the intestinal barrier, and modulating immune responses. Disruptions to this microbiota can exacerbate GI and immune system dysfunction, potentially leading to severe outcomes. This review examines the mechanisms underlying BGA dysfunction following TBI, focusing on the pathways contributing to this dysregulation. Additionally, it discusses therapeutic strategies aimed at mitigating gut microbiota dysbiosis. Potential interventions include approaches to restore microbial balance, enhance gut barrier integrity, and support immune modulation. By targeting these areas, therapies may reduce the systemic effects of TBI and improve patient outcomes.
Keywords: traumatic brain injury; brain–gut axis; microbiome; dysbiosis; therapeutic interventions